P300 Overweight and obesity in Inflammatory Bowel disease: epidemiology, disease course and treatment outcomes. (30th January 2023) - Khemiri, W; Ben Mustapha, N; Ben Safta, N; Serghini, M; Laabidi, S; Fekih, M; Labidi, A; Boubaker, J
Abstract: Background: The incidence of Inflammatory Bowel Disease (IBD) is increasing in parallel with overweight and obesity. Contrary to conventional belief, a considerable number of IBD patients are at least overweighted. This may contribute to the development of IBD. The objectives of our study were to estimate the prevalence of overweight and obesity in IBD and to compare the epidemiological, evolutive and therapeutic profiles in these patients with those of a BMI (Body Mass index) of less than 25 kg/m². Methods: We conducted a retrospective, descriptive and comparative study including patients hospitalized for IBD over a 9-year period [January 2011-January 2020]. Patients with less than 2 years of follow-up were excluded. Patients with a BMI of less than 25kg/m² represented group 1 and patients with a BMI ≥ 25kg/m² represented group 2. Results: We included 225 men and 227 women. We enrolled 341 patients diagnosed with Crohn's disease (CD) and 111 patients with ulcerative colitis (UC). BMI was less than 18.5kg/m², between 18.5 and 25kg/m², between 25 and 30kg/m² and ≥30kg/m² in 27.1%, 48.3%, 19.1% and 5.5% of the patients respectively, resulting in 340 patients in group 1 and 112 patients in group 2. The mean age at diagnosis was 36.15 ± 12.74 years. It was significantly lower in group 1 (32.24 years vs 40.06 years, p<0.001). Smoking was noted in 34.1% of patients and 15.9% were alcohol users, the difference in these habits was not significant between the two groups. Diabetes and hypertension were significantly higher in group 2 (p<0.001 and p=0.002 respectively). The percentage of patients followed up for UC was higher in group 2 (31.8% vs 20.54%, p=0.04). For CD, patients with upper GI tract involvement were more numerous in group 1, without a significant difference between the two groups (16.22% vs. 7.8%, p=0.068). The mean level of albumin was lower than normal in both groups (31.57g/L in group 1 and 34.02g/L in group 2) with a significantly lower level in group 1 (p=0.002). The use of surgical treatment was significantly higher in group 1 (p=0.003). However, there was no significant difference between the two groups in the use of corticosteroid, immunosuppressive agents, anti-TNFα therapy and the responses to these different treatments. The maximum duration of hospitalization was statistically longer in group 1 compared to group 2 (20.95 days vs. 15.32 days, p=0.003). The ratio of years of follow-up to years of active disease was significantly higher in group 2 (5.8 vs. 4.7, p=0.014), reflecting a better disease course in group 2. Conclusion: In our series, one fifth of the patients were either overweighted or obese. IBD in these patients was, overall, less severe.